Pharmacotherapeutic Analysis and Prescription Pattern of Antihypertensive Drugs Dispensed at Community Pharmacies in Palestine (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
The objective of this study is to explore the influence of current therapeutic recommendations on the prescribing trends of anti-hypertensive drugs in general medical practice in Palestine. Five hundred and seventy four anti-hypertensive prescriptions were analyzed. The percentage of mono-therapy prescriptions was 48.25% and that for combinational therapy prescriptions was 51.75%. Among the mono-therapy prescriptions, b- blockers were the most commonly prescribed, while diuretics were under-utilized. Inappropriate dose strength of atenolol was seen in mono-therapy prescriptions. Expensive and newer angiotensin converting enzyme inhibitor drugs (ACE-I) and calcium channel blocking drugs (CCB) were frequently seen in mono therapy prescriptions. Among the combinational therapy, the b-blockers / diuretics was most common. Irrational combinational therapy of b-blockers / ACE-I was noticed. Use of modern and new CCB, ACE-I and angiotensin II type 1 receptor antagonists (AT1-RA) was seen in both mono therapy and combinational therapy. The overuse of nonprefered drugs and the under-use of prefered medications is indicative that education of JNC VI guidelines for physicians and health professionals in Palestine is needed.